2017
DOI: 10.3389/fphys.2017.00237
|View full text |Cite
|
Sign up to set email alerts
|

Early Changes in Glutamate Metabolism and Perfusion in Basal Ganglia following Hypoxia-Ischemia in Neonatal Piglets: A Multi-Sequence 3.0T MR Study

Abstract: The excitotoxicity of glutamate metabolism as well as hemodynamic disorders of the brain are both risk factors for neonatal hypoxic–ischemic brain damage (HIBD). In the present study, changes in glutamate metabolism in the basal ganglia were detected by proton magnetic resonance spectroscopy (1H-MRS) at 0–6, 8–12, 24–30, and 48–60 h after the induction of hypoxia-ischemia (HI) in newborn piglets. Meanwhile, correlation analysis was performed by combining the microcirculatory perfusion informations acquired by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
1
7
0
1
Order By: Relevance
“…FETAL CENTRAL NERVOUS SYSTEM (CNS) injury is the important reason for perinatal death and disability . For example, basal ganglia region (BGR) injury is the main cause of permanent dysneuria and cerebral palsy in the perinatal period . Early detection and quantitative assessment of fetal CNS injury is the key for clinicians to make effective interventions.…”
mentioning
confidence: 99%
“…FETAL CENTRAL NERVOUS SYSTEM (CNS) injury is the important reason for perinatal death and disability . For example, basal ganglia region (BGR) injury is the main cause of permanent dysneuria and cerebral palsy in the perinatal period . Early detection and quantitative assessment of fetal CNS injury is the key for clinicians to make effective interventions.…”
mentioning
confidence: 99%
“…Similar results were observed in the cerebrospinal fluid (CSF) or cerebral areas of patients after a traumatic brain injury [53,54]. Higher levels of glutamate have also been described in the CSF of infants correlating with the severity of hypoxic-ischemic (H-I) encephalopathy [55], and indeed levels of glutamate remain elevated for days in animal models of pre-term H-I injury [56,57,58]. Glutamate excitotoxicity is also an important event in chronic neurodegenerative diseases [49].…”
Section: Introductionmentioning
confidence: 60%
“…The study of Perciaccante et al ( 38 ), a study in which the population underwent intravital microscopy, suggests that hypothermia does not affect cerebral arteriolar dilatation to NMDA during and following ischemia, indicating that the cerebroprotective effects of hypothermia therapy are not mediated by NMDA. The study of Dang et al ( 31 ), using proton magnetic resonance spectroscopy ( 1 H-MRS) and diffusion-weighted imaging (DWI), showed that the glutamate level in the basal ganglia underwent a “two-phase” change after HI: first a rise in glutamate after 0–6 h and secondly a rise in glutamate after 24–30 h, due to reperfusion injury.…”
Section: Resultsmentioning
confidence: 99%